Crumbs3 is a critical factor that regulates invasion and metastasis of colon adenocarcinoma via the specific interaction with FGFR1. Issue 10 (29th April 2019) - Iioka, Hidekazu; Saito, Ken; Sakaguchi, Masakiyo; Tachibana, Taro; Homma, Keiichi; Kondo, Eisaku
Abstract : Epithelial cell polarity regulator Crumbs3 ( Crb3 ), a mammalian homolog within the Drosophila Crb gene family, was initially identified as an essential embryonic development factor. It is recently implicated in tumor suppression, though its specific functions are controversial. We here demonstrate that Crb3 strongly promotes tumor invasion and metastasis of human colon adenocarcinoma cells. Crb3 centrality to tumor migration was supported by strong expression at invasive front and metastatic foci of colonic adenocarcinoma of the patient tissues. Accordingly, two different Crb3 ‐knockout (KO) lines, Crb3‐ KO ( Crb3 −/−) DLD‐1 and Crb3‐ KO WiDr from human colonic adenocarcinomas, were generated by the CRISPR‐Cas9 system. Crb3‐KO DLD‐1 cells exhibited loss of cellular mobility in vitro and dramatic suppression of liver metastases in vivo in contrast to the wild type of DLD‐1. Unlike DLD‐1, Crb3‐KO WiDr mobility and metastasis were unaffected, which were similar to wild‐type WiDr. Proteome analysis of Crb3‐coimmunopreciptated proteins identified different respective fibroblast growth factor receptor (FGFR) isotypes specifically bound to Crb3 isoform a through their intracellular domain. In DLD‐1, Crb3 showed membranous localization of FGFR1 leading to its functional activation, whereas Crb3 bound to cytoplasmic FGFR4 in WiDr without FGFR1 expression, leading to cellular growth. Correlative expression between Crb3 and FGFR1 was consistently detected in primary and metastatic colorectal cancer patient tissues. Taking these together, Crb3 critically accelerates cell migration, namely invasion and metastasis of human colon cancers, through specific interaction to FGFR1 on colon cancer cells. Abstract : What's new? Epithelial cell polarity regulator Crumbs3 (Crb3) was initially identified as an essential embryonic development factor. More recently, it has been implicated in tumor suppression, though its specific functions remain controversial. Here, the authors demonstrate that Crb3 strongly promotes tumor invasion and metastasis of human colon adenocarcinoma cells. They identify among the binding partners of Crb3 the FGF receptors family, which is pivotal to tumor cell dynamics including proliferation, migration, and differentiation. Crb3 colocalizes with FGFR1 to activate downstream signaling and critically accelerate tumor migration and metastasis of human colon cancers.